Pengaruh Komunikasi Organisasi dan Kompetensi Digital terhadap Kinerja Pegawai melalui Motivasi Kerja sebagai Variabel Intervening pada Kantor Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) Kabupaten Mukomuko - Noviyudini, Azella; Kumbara, Vicky Brama; Nadilla, Nia (TSAQOFAH, 2026)
This study is motivated by the need to improve employee performance in the public sector through organizational communication management and the strengthening of digital competence, particularly within the Dinas Pekerjaan Umum dan Penataan Ruang (PUPR) of Mukomuko Regency. The study aims to analyze the effects of organizational communication and digital competence on employee performance, with work motivation as an intervening variable. A quantitative approach was employed using a survey method involving 85 employees as respondents. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to examine the direct and indirect relationships among the variables. The results show that organizational communication has a positive but not significant effect on work motivation, whereas digital competence has a positive and significant effect on work motivation. Organizational communication and digital competence both have positive and significant effects on employee performance, and work motivation also has a positive and significant effect on employee performance. The mediation test indicates that work motivation does not mediate the effect of organizational communication on employee performance but significantly mediates the effect of digital competence on employee performance. These findings indicate that strengthening digital competence is a key factor in fostering employee motivation and performance, while the quality and effectiveness of organizational communication still need to be improved to contribute more optimally to work motivation. This study provides practical implications as a basis for formulating human resource development policies grounded in digital transformation in the public sector.